Analisis Kesulitan Belajar Mahasiswa dalam Mempelajari Materi Medan Vektor pada Mata Kuliah Kalkulus Vektor (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to investigate the obstacles faced by students in understanding vector field material in the Vector Calculus course. The basis of this study is the low understanding of students regarding abstract concepts in vector calculus, particularly related to vector fields, the del operator, gradients, and directional derivatives. The method applied in this research is qualitative, utilizing questionnaires distributed to three students from the fourth semester. The research findings indicate that students encounter major challenges in visualizing vector fields in three-dimensional space, understanding the differentiation process related to gradients, and associating directional derivatives with gradients. Several factors contributing to these difficulties include a lack of variation in practice problems and a minimal understanding of basic mathematical concepts. The results of this study highlight the need for a learning approach that focuses more on strengthening concepts, the use of visual media, as well as its application in real contexts so that students can build a deeper understanding of vector field material. The results of this study are expected to provide input for the development of more effective and beneficial vector calculus teaching methods.